Construction of The Meaning of “Aku memaafkan” in the Lyrics of the Song “Jernih” By Kunto Aji - Diva Rahmanto; Khaerudin Imawan; Aghnia Dian Lestari (Journal of Science and Education (JSE), 2026)
Music plays an important role as a medium of communication in conveying reflective and emotional messages through lyrics that can be interpreted personally by listeners. This is in line with Kunto Aji's statement about the human tendency to often forget the importance of talking to oneself, and to simply enjoy songs without understanding their deeper meaning. This study aims to analyze the construction of meaning of “Aku memaafkan” in the lyrics of Kunto Aji's song “Jernih”. This study uses a descriptive qualitative method, with Ferdinand De Saussure's semiotic approach and through intrapersonal communication. Data were collected through lyric analysis and interviews with listeners. The results show that the phrase “Aku memaafkan” is constructed as a meaning of releasing inner wounds, freeing oneself from past trauma, and healing efforts to achieve inner peace. The repetition of the phrase “Aku memaafkan” serves as an affirmation that strengthens an individual's internal dialogue in dealing with emotional conflicts. Listeners' interpretations reveal that the meaning of “Aku memaafkan” is not only understood symbolically but also internalized as a form of self-reflection. This study concludes that a song not only functions as an artistic work but can also be an effective communication medium in assisting the process of forgiveness.